1998
DOI: 10.1021/ja980684z
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation and Reactivity of Phenyllithium Solutions

Abstract: Phenyllithium forms a mixture of tetramer and dimer in ether. Complete conversion to dimeric solvates is achieved by the addition of THF, dioxolane, DME, or TMEDA in near stoichiometric amounts. The addition of 2,5-dimethyltetrahydrofuran favors dimer, but tetramer is still detectable at 14 equiv of cosolvent. PMDTA converts PhLi to monomer in ether. In THF, PhLi is a mixture of dimer and monomer. Addition of TMEDA forms a series of complexes, but the dimer/monomer ratio is essentially unaffected. PMDTA and HM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
149
2

Year Published

1999
1999
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(162 citation statements)
references
References 58 publications
11
149
2
Order By: Relevance
“…It is known that phenyllithium is a mixture of dimer and monomer in THF; 11 concerning pyridyllithiums, such studies were not reported (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…It is known that phenyllithium is a mixture of dimer and monomer in THF; 11 concerning pyridyllithiums, such studies were not reported (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…The addition of TMEDA in THF has little if any effect on the monomer/dimer ratio, but forms a series of complexes with phenyllithium. [19] These changes in the structure of the phenyllithium may explain, in this case, the observed increase in reactivity. Thus, with three equivalents of TMEDA per aryllithium, condensation of the aryllithiums 4 d and 4 g onto the carbonyl at position 17 of estrones 1 and 2 occurs in 60 % yield to give the arylestradiols 7, 9, or 12.…”
Section: Activation By Tmedamentioning
confidence: 93%
“…The crude product was purified by silica gel column chromatography with toluene/ethyl acetate (4:96) as eluent and crystallized in ether/pentane (1:9) to give 17 as a white solid (32 mg, 76 %). 17a-(4'-Methoxyphenyl)estra-1,3,5(10)-trien-3,17b-diol (19): A mixture of 6 and estrone 1 (155 mg), resulting from preparation of 6, was dissolved in methanol (15 mL) and THF (4.5 mL) containing Pd/C 10 % (25 mg) in suspension. The reaction mixture was stirred under atmospheric pressure of hydrogen for 17 h. After filtration and evaporation of the solvents, the residues were crystallized from dichloromethane to give 19 as a white solid in 68 % yield (with low solubility in various solvents).…”
Section: Chemistrymentioning
confidence: 99%
“…The results 9 for 3,5-di-t-butyl-phenyl lithium, 1, are illustrative ( Figure 2). Reich and coworkers 10 have provided a benchmark study of the power of nmr to characterize organolithium solutions. They studied the monomer/dimer/tetramer equilibria of phenyl lithium as a function of solvent and temperature.…”
Section: Chemical Shiftmentioning
confidence: 99%
“…Studies of the solvation of phenyl lithium from the relative shifts of the ring carbons provides an excellent example. 10 The Schade and Boche study 34 of solvation of a benzyl lithium discussed under 2D methods is another.…”
Section: Chemical Shift and Charge Densitymentioning
confidence: 99%